Global revision of the dulotic ant genus Polyergus (Hymenoptera: Formicidae, Formicinae, Formicini) - Trager, James C. (Zootaxa, 2013)
The genus Polyergus is characterized, and all valid species reinstated and re-described, and five new species described, based on morphometric, ecological, host-association, and biogeographic characteristics. Polyergus contains 14 species: 3 Palaearctic, 11 Nearctic. The rufescens group comprises western Eurasian rufescens Latreille 1804 including its former eastern subspecies tianschanicus Kuznetsov-Ugamsky 1927 new synonymy, and the following American species, informally called the breviceps complex: breviceps Emery 1893 sensu stricto, revised status, bicolor Wasmann 1901 new status, mexicanus Forel 1899 new status, topoffi new species, and vinosus new species. The lucidus group comprises longicornis M. R. Smith 1947 new status, lucidus Mayr 1870 sensu stricto, revised status, montivagus Wheeler 1915 new status, oligergus new species, ruber new species, and sanwaldi new species. The samurai group comprises two blackish forms: the western Asian P. nigerrimus Marikovsky 1963 and eastern Asian P. samurai Yano 1911. Polyergus texana Buckley 1866 is excluded from Polyergus.